Law, Empire, and the Sultan - Omar Anchassi (International Institute of Islamic Thought, 2020)
Though their temporal origins, format, and organization betray them as distinctively ‘modern’, the Late Ottoman Mecelle and its commentaries are indebted to a juristic culture that was already by the period in question well over a millennium old. In important ways, their indebtedness to this culture is profound; until recently, however, the degree and nature of this influence had not been properly acknowledged. The monograph under review is a meticulous and formidably-learned study of continuity and change in post-classical Islamic law.